Kesehatan Mental dan Strategi Koping Dalam Perspektif Budaya: Sebuah Studi Sosiodemografi di Kampung Aminweriri - Chintya M.G Manullang; Yulius Yusak Ranimpi; Rama Tulus Pilakoannu (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
Mental health is a state of a person who does not experience the feeling of guilt towards him/herself, have a realistic estimate, can receive a deficiency or weakness, the capability of facing the problems and have satisfaction and happiness in his/her life. The prevalence of severe psychiatric in Indonesia experienced a significant increase in the year 2013 only 1.7% to 7% in the year 2018. In mental health, cultural factors also play an important role. A person is said to be healthy or mentally ill depends on culture. There are two types of coping according to Lazarus and Folkmannamely problem focused coping (PFC) and emotion focus coping (EFC). In the PFC, the individual in dealing with the problem would be the logical thinking and trying to solve the problems of the positive. Whereas in the EFC, individuals assuage the emotions evoked by the stressor (source of stress) without trying to change the situation. Describe the mental health and cultural perspectives in coping strategy based on the profile of the sociodemographic community in  Aminweri village. A qualitative approach to data collection techniques as well as phenomenology with structured interviews and documentation. Determination of the participant determined by purposive sampling technique. Obtained 3 huge themes: acquired memory, emotion regulation strategies and coping. Generally variable sociodemographic connectedness with a decline in memory, emotion regulation, shared the coping community  Aminweri Village  and there is the influence of the culture of Biak.